Constraint Analysis of Paddy Seed and Grain Production in Karimnagar District of Telangana Using Garrett’s Ranking Technique - Jayaprada Y.; T Lavanya; Santhosha Rathod (International Journal of Economics (IJEC), 2023)
The present study was conducted in Karimnagar purposively selected district of Telangana to identify the constraints perceived by farmers in grain and seed production of hybrid and open pollinated varities of paddy . From this district three mandals i.e Vinavanka mandal, Manakondur mandal and Shankarpatnam mandal, were selected randomly among seed growing mandals for collecting primary data. From each mandal, one village was selected as a sample i.e Elbaka village (Vinavanka mandal), Utoor village (Manakondur mandal) and Kannapur village (Shankarpatnam mandal). Sampling was done covering all farm size groups. In every chosen village, a total of 60 farmers were selected for sampling. This selection was designed to encompass 20 farmers engaged in the production of Hybrid seeds, another 20 involved in the production of OPV seeds, and an additional 20 farmers focused on grain production. Consequently, the complete sample consisted of 180 farmers distributed among the three villages. Garrett’ ranking technique was adopted to analyze the constraints as perceived by the respondents in Grain and seed production of paddy. The results revealed that major constraints perceived by rice growers were unfavourable weather conditions which ranked first with Garrett mean score around 85, followed by higher labour wage.